Social Effectiveness: A 30-Year Review of the Rehabilitation Counseling Literature. (October 2016) - Phillips, Brian N.; Deiches, Jon; Morrison, Blaise; Kaseroff, Ashley A.
The ability to effectively manage social interactions is key to achieving many life goals. A substantial amount of research has been conducted in rehabilitation counseling and rehabilitation psychology that includes a consideration of some aspect of social effectiveness. The purpose of this study was to collect and synthesize the past 30 years of rehabilitation counseling and rehabilitation psychology research addressing aspects of social effectiveness. A total of 13 terms (e.g., interpersonal skills, social competence, social functioning, and soft skills) were used to search six of the most prominent rehabilitation counseling and rehabilitation psychology journals from the period January 1982 to May 2013. A total of 608 articles were identified as including at least one of the search terms, with 175 using a search term prominently and the other 433 only passively. Social skills, social functioning, and social competence were among the most frequently used search terms, accounting for almost 90% of all used terms. It was found that social effectiveness constructs were rarely defined and often used interchangeably. Twenty-nine interventions studies had been published in the 30-year period. Results reflect a substantial and useful body of literature in this area of research while also conveying an opportunity for the development of a more systematic, unified, and theory-driven approach to understanding and addressing aspects of social effectiveness.